"Thank You for Listening": An Exploratory Study Regarding the Lived Experience and Perception of Medical Errors Among Those Who Receive Care. (April 2022) - Terry, Daniel; Kim, Jeong-ah; Gilbert, Julia; Jang, Sunny; Nguyen, Hoang
The issue of medical errors, or adverse events caused within a health care context or by a health care provider, is largely under-researched. While the experience and perspective of health care professionals regarding medical errors have been explored, little attention is paid to the health care consumers regarding their perceptions and experiences. Therefore, there is a need to better understand the public's views on medical errors to enhance patient safety and quality care. The current study sought to examine Australian public perceptions and experiences, especially concerning what errors had occurred, the perceived sources of the errors, and if the errors had been reported. This paper reports the qualitative findings of an online survey for Australian residents who have accessed or received medical services at any time in Australia. Responses from 304 surveys were analyzed and discussed, including demographic information and key themes about medical errors, which were categorized into engagement and patients' voices being heard, the quality of care being provided, and the system's accountability. Based on the findings, the study highlights the importance of effective health professional–patient communication, enhanced capacity to deliver high quality care, and improved mechanism for error reporting and resolution where patients feel safe and confident about positive changes being made.